2013
DOI: 10.1172/jci67315
|View full text |Cite
|
Sign up to set email alerts
|

Retinal angiogenesis suppression through small molecule activation of p53

Abstract: Neovascular age-related macular degeneration is a leading cause of irreversible vision loss in the Western world. Cytokine-targeted therapies (such as anti-vascular endothelial growth factor) are effective in treating pathologic ocular angiogenesis, but have not led to a durable effect and often require indefinite treatment. Here, we show that Nutlin-3, a small molecule antagonist of the E3 ubiquitin protein ligase MDM2, inhibited angiogenesis in several model systems. We found that a functional p53 pathway wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 26 publications
0
22
0
Order By: Relevance
“…Neonatal C57B mice were given peptide (either KAI or CT23, 10 mg/kg dissolved in PBS) or PBS vehicle at the day of birth (postnasal day 0) and subsequent days (postnasal days 1 to 4) daily s.c. under eyelid as previously described. 33 At postnatal day 6, the retina was isolated and stained with anti-CD31 antibody (Abcam) as previously described. 34…”
Section: Postnatal Retina Angiogenesismentioning
confidence: 99%
“…Neonatal C57B mice were given peptide (either KAI or CT23, 10 mg/kg dissolved in PBS) or PBS vehicle at the day of birth (postnasal day 0) and subsequent days (postnasal days 1 to 4) daily s.c. under eyelid as previously described. 33 At postnatal day 6, the retina was isolated and stained with anti-CD31 antibody (Abcam) as previously described. 34…”
Section: Postnatal Retina Angiogenesismentioning
confidence: 99%
“…Mechanistically, we found that β-catenin inhibits p53 activity in SMCs, and loss of this function impaired artery formation. Interestingly, postnatal increase in p53 activity inhibits angiogenesis 48 . Thus, repression of p53 activity appears necessary for developmental vascular maturation and for postnatal angiogenesis; our findings point to this as a key function of SMC β-catenin during development.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Ambati et al have also examined the role of p53 in retinal angiogenesis and have found disruption of p53 transcriptional network can abolish the anti-angiogenic activity of Nutlin3 (drugs commonly used in cancer). Even though the group did not show any relation with DcR1 or DcR2 receptors the role of DcR1 in apoptotic process could be examined in the context of p53 processes18. Several mouse models for retinal degeneration have been established by genetic manipulations in several retinal related genes and also created by light injury of retinal layers in which apoptosis contributes towards photoreceptor cell death192021.…”
Section: Discussionmentioning
confidence: 99%